NUMERICAL MODELS AS TOOLS TO UNDERSTAND THE DYNAMICS IN BAYS: CASE OF STUDY CHETUMAL BAY, QUINTANA ROO - Cueva, David Avalos (Universidad Autónoma Indígena de México, 2018)
.In this study performed the simulation of currents generated by the wind on the Bay of Chetumal, Quintana Roo through the use of a stationary shallow-water model. A homogeneous climatic wind was used for the entire Bay, with a velocity of 3m·s-1 , and directions North, South, Northeast, Northwest, East, Southeast, Southwest and West. The results showed a rather complex dynamics in Chetumal Bay, in which important turns were observed in deep areas, with speeds reaching up to 13 cm·s-1 .